(untitled) (Western European Journal of Medicine and Medical Science, 2026)
This article examines the functional analysis of texts in linguistics and its significance in understanding language as a communicative and social phenomenon. Functional text analysis focuses on the relationship between language structures and their communicative purposes within specific contexts. The paper explores the theoretical foundations of functional linguistics, the classification of text functions, discourse structures, contextual meanings, and pragmatic features. Special attention is paid to the role of cohesion, coherence, communicative intention, and stylistic variation in textual interpretation. The article also discusses the contributions of prominent linguists to functional approaches and analyzes the practical applications of text functional analysis in education, translation studies, discourse analysis, media communication, and intercultural interaction. The study concludes that functional text analysis plays a crucial role in modern linguistics by enabling researchers to interpret language beyond grammatical structures and understand the interaction between language, society, and communication